Evaluation of East African highland banana land races and hybrids for resistance to banana nematodes in semiarid Uganda - Wasukira, A.; Coyne, Danny L.; Dubois, T.; Dusabe, J.; Pillay, M.; Lorenzen, J.H. (2008)
Radopholus similis, Helicotylenchus multicinctus and Meloidogyne spp. are among the major nematode pests of banana worldwide. Nematode management through exploitation of genetic sources of resistance is widely encouraged, especially in resource poor countries. A number of hybrids have been developed and assessed for resistance to nematodes under screenhouse conditions and on station. The current study was designed to test the resistance of the genotypes, both land races and hybrid selections that had exhibited some nematode resistance in screening exercises, in a semi-arid location. Peeled and hot water treated suckers of 51 banana genotypes were planted out into the field in Eastern Uganda, (semi-arid ecosystem) where the natural nematode field populations represented the inoculum. The plot management was divided into one of high or low, represented by application of spear grass mulch (~15 cm depth every six months) or no mulch, respectively